Enhancement of confidentiality and integrity during big data transmission using a hybrid technique - Bhattacharjee, S. (Asian Research Publishing Network, 2015)
The most fundamental issues of any data transmission over the internet are maintaining its confidentiality and integrity. The data integrity may suffer due to unauthentic interferences or various transmission errors. These issues increase when the transmitted file size is extremely large. Many researches have been performed to address these issues individually. However, there is no integrated technique being suggested in previous researches to address both these issues in big data transmission system. Therefore, we have proposed a new error control technique and a unique LSB (Least Significant Bit) based audio steganography technique and combined them to develop a hybrid technique. The proposed control technique is designed to remove all discrete or continuous data errors and to provide a backup system for accidental data loss. The proposed steganography technique is developed to offer high confidentiality, protect various security attacks and to enhance robustness against various errors. The result section shows its capacity to produce robustness against various errors in terms of signal to noise ratio, uncorrectable error rate and percentage of data loss. The confidentiality level is shown by calculating frequency and amplitude difference between the original and stego samples. Its capacity to protect various attacks has been tested by calculating entropy values. All tests are performed in wireless environment using different types and different sizes of input files.